Draft Eighth Plan 1990-95 and Draft Annual Plan 1991-92 Vol-I Introduction and Statements Government of Tripura - Planning Commission (Planning Commission, 1990)
The unemployment is mounting up. Even as per records in the Live Register, it will appear that the number of educated unemployed which was 69,618 as on December, 1980, is 1,56,727 on December, 1989. Besides, there are vast number of unregistered unemployed in rural areas. Using N.S.S. date of 38th round (1983-84), it appears that during the Eighth Five Year Plan, addition to labour force will be about 74,000.
Government of Tripura